(untitled) (Al-Academy, 2016)
The Comedy of patterns dramas that gave Representative possibilities of advanced functionality and wide being dependent on the diversity performance piece , which is intended to provoke laughter at the receiver, through the diversity of genres performing between dancing and singing and Albantomaim and other methods that have made them distinct from the species dramas other being enabled Representative in dealing with all roles across mature and adaptation of his tools of physical and vocal , as the comedy discusses the societal issues many have a factor of psychological and behind their platforms as a tool face is not directly give way to vent citizen injustice and disadvantages of humans and these conditions need to techniques of physical and sound alert for I start action and reaction .The researcher found the results to some of them: -1-rely on the capabilities of Representative expressive physical and vocal performance in the comedy role for the production of speech and audio visual contents of an intellectual and aesthetic.2-enables the comedian of the diversity of verbal discourse between (poetry, prose and song) and this is what gives him wider areas in the multiplicity of meaning